Influence of morphological changes in a lagoon flooding extension: case study of Ria de Aveiro (Portugal) - Lopes, Carina L. (2018)
Coastal lagoons are interface zones where land, water and atmosphere interact in a dynamic balance that is constantly being changed by natural and human influence. The hydrodynamics and morphology of these coastal systems continuously adapt to changes in the forcing agents and show a complex interconnection. Worldwide studies show that tidal propagation is strongly dependent on local morphologic features. Attending to these concerns, the present study aims to assess the changes in flooding extension at Ria de Aveiro, as well as in the tidal prism, induced by local morphological modifications. The analysis of the topo-hydrography available for the Ria de Aveiro, comprising two general surveys carried out in 1987/88 and 2011 and two updates of the inlet bathymetry performed in 2001 and 2012, shows the deepening of the lagoon main channels and of the inlet evolving region. A flooding assessment of the lagoon margins and the determination of the tidal prism were performed applying the hydrodynamic model ELCIRC considering the four morphologic configurations described and different tidal conditions. The numerical results show the importance of lagoon morphological changes, which induce an increase of about 16% between 1987/88 and 2012 in the lagoon flooded area for spring tide. The new flooded regions correspond to the margins of S.Jacinto channel head and lagoon central areas. Additionally, the tidal prism results evidence a redistribution of the water volume flowing into the lagoon among their main channels during the period under analysis.